A critical discourse analysis of hemingway's for whom the bell tolls implementing hallidayan functional grammar - HADDAD, Nabil (University of Mostaganem, 2015)
The present dissertation aims at providing a critical discourse analysis of Ernest Hemingway‘s For Whom the Bell Tolls, within the framework of Systemic Functional Grammar of Halliday. More precisely, we apply Halliday‘s Register Theory (Context of Situation). Three steps are followed to attain the objective of our investigation. Firstly, we have dealt with the perspective which is Critical Discourse Analysis –from which the novel is approached. Related key terms to discourse studies such as text, discourse and texture have been introduced. Secondly, we have introduced the methodological research tool: Systemic Functional Grammar of Halliday. Linguistic theoretical background is provided so as to be familiar with this research tool and related terminology. Thirdly, we put into practice the Register Theory by addressing the context of the extracted example in its three variables: the field, the tenor, and the mode. Within the frame of discourse analysis, this study also addresses the text of the novel critically in quest for potential bias such as ethnocentrism, sexism, stereotyping and anti-Semitism. Each of the three components of context will raise a question. Field has to do with the content or the topic in which the participants are involved. Tenor has to do with the status and the relationship between the participants. Mode deals with the medium or language by which interaction between the participants is attained. Taking into consideration the definition of bias and its potential forms, these three variables proved to be very useful as to revealing the extent to which the author is biased or not. The application of the Register Theory has revealed the presence of ethnocentrism and stereotyping while sexism and anti-Semitism are absent; hence, using this theory may well unveil some of the hidden intensions of the writer. These may seem quite opaque to a layperson